2003
DOI: 10.1108/03074350310768300
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic factors and stock prices in the emerging Cypriot equity market

Abstract: This study examines the relationships between macroeconomic factors and stock prices in Cyprus. Estimating a reduced form Vector Autoregressive model (VAR) we determine Granger causality between stock returns and the predictor variables. We find strong evidence of predictability (which implies inefficiency) in stock returns, which is similar to the pattern observed in developed stock markets. In common with prior studies in this area, we cannot use our results as evidence of market inefficiency or deficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 1 publication
2
17
0
5
Order By: Relevance
“…More and more researches take place in developing financial markets, including the works written by Mookerjee and Yu (1997), Maysami and Koh (2000), who analyzed the dependence of changes of stock market indices quoted in Singapore stock market from macroeconomic factors, also Kwon and Shin (1999), who analyzed such connection in the stock market of South Korea, and Chong and Goh (2004), who analyzed the stock market in Malaysia. An influence of macroeconomic indicators on the country's stock market index in developing stock markets is analyzed in the works with a focus on Athens (Dritsaki 2005) or Cyprus (Tsoukalas 2003). There is a lack of such type of researches especially in less developed stock markets in East and Central Europe, including the Baltic stock market Pilinkus and Boguslauskas 2009).…”
Section: Introductionmentioning
confidence: 99%
“…More and more researches take place in developing financial markets, including the works written by Mookerjee and Yu (1997), Maysami and Koh (2000), who analyzed the dependence of changes of stock market indices quoted in Singapore stock market from macroeconomic factors, also Kwon and Shin (1999), who analyzed such connection in the stock market of South Korea, and Chong and Goh (2004), who analyzed the stock market in Malaysia. An influence of macroeconomic indicators on the country's stock market index in developing stock markets is analyzed in the works with a focus on Athens (Dritsaki 2005) or Cyprus (Tsoukalas 2003). There is a lack of such type of researches especially in less developed stock markets in East and Central Europe, including the Baltic stock market Pilinkus and Boguslauskas 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that there is a significant relationship between macroeconomic variables and stock market (Bilson et al, 2001;Hondroyiannis & Papapetrou, 2001;Ibrahim & Aziz, 2003;Tsoukalas, 2003;Maysami et al, 2004;Coleman & Tettey, 2008;Horobet & Dumitr, 2009;Buyuksalvarci, 2010;Geetha et al, 2011;Ali, 2011;Rafique et al, 2013;Lakshmi & Tuwajri, 2014;Wongbangpo & Sharma, 2002;Masuduzzaman, 2012;& Ray, 2012). Other found no significant relationship between macroeconomic variables and stock market (Mohammad et al, 2009;Bhattacharya et al, 2001;Ali, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Taxa de juros (ver Abdullah e Hayworth, 1993;Kwon, Shin e Bacon, 1997;Tsoukalas e Sil, 1999;Muradoglu, Taskin e Bigan, 2000;Fifield, Power e Sinclair 2002;Burmeister, Roll, e Ross, 2003;Mavrides, 2003;Dritsaki, 2005); • Taxa de inflação (ver Abdullah e Hayworth, 1993;Kwon, Shin e Bacon, 1997;Muradoglu, Taskin e Bigan, 2000, Fifield, Power e Sinclair 2002, Tsoukalas, 2003Burmeister, Roll, e Ross, 2003;Mavrides, 2003;Dritsaki, 2005), • Taxa de câmbio (ver Kwon, Shin e Bacon, 1997, Muradoglu, Taskin e Bigan, 2000Ibrahim, 2000;Tsoukalas, 2003;Mishra, 2004). A taxa de inflação foi representada pelo Índice Nacional de Preços ao Consumidor (INPC).…”
Section: Variáveisunclassified